2022
DOI: 10.1002/mrm.29304
|View full text |Cite|
|
Sign up to set email alerts
|

Point‐of‐care magnetic resonance technology to measure liver fat: Phantom and first‐in‐human pilot study

Abstract: Purpose To assess feasibility and accuracy of point‐of‐care (POC) NMR‐proton density fat fraction (PDFF) in phantoms and in a human pilot study in a POC setting. Methods POC NMR (LiverScope, Livivos, San Diego CA) PDFF measurements were obtained of certified phantoms with known PDFF values (0%‐40%). In an institutional review board‐approved, Health Insurance Portability and Accountability Act‐compliant prospective human study, a convenience sample of participants from an obesity clinic was enrolled (November 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…These techniques are expected to play an important role in the context of abbreviated MRI in combination with PDFF measurements for the evaluation of diffuse liver diseases, including NAFLD and NASH [ 26 52 ]. Finally, improving the cost-effectiveness of these applications by adopting low-field point-of-care MRI [ 53 ] will help to further popularize the implementation of MRI for the evaluation of diffuse liver disease.…”
Section: Hepatic Fibrosismentioning
confidence: 99%
“…These techniques are expected to play an important role in the context of abbreviated MRI in combination with PDFF measurements for the evaluation of diffuse liver diseases, including NAFLD and NASH [ 26 52 ]. Finally, improving the cost-effectiveness of these applications by adopting low-field point-of-care MRI [ 53 ] will help to further popularize the implementation of MRI for the evaluation of diffuse liver disease.…”
Section: Hepatic Fibrosismentioning
confidence: 99%
“…[63] Point-of-care biochemical tests and imaging devices have been actively explored as potential options to substantially improve receipt of the regular screening examination, particularly in developing regions with limited access to medical care. [64][65][66][67] These new technologies could be combined with software as a medical device (SaMD), incorporating artificial intelligence (AI) and machine learning/deep learning (ML/DL) for widespread application. [68] Several promising examples are overviewed in the following sections.…”
Section: Emerging Technologies/methodologies With Potential Utility I...mentioning
confidence: 99%
“…A functional in vivo genetic screening suggested that there may be a new class of HCC risk‐associated DNA variants (somatic DNA mutations in PKD1 [encoding polycystin 1, transient receptor potential channel interacting], KMT2D [encoding lysine methyltransferase 2D], and ARID1A [encoding AT‐rich interaction domain 1A] genes) in cirrhotic liver that confers a protective effect against carcinogenesis 63. Point‐of‐care biochemical tests and imaging devices have been actively explored as potential options to substantially improve receipt of the regular screening examination, particularly in developing regions with limited access to medical care 64–67. These new technologies could be combined with software as a medical device (SaMD), incorporating artificial intelligence (AI) and machine learning/deep learning (ML/DL) for widespread application 68.…”
Section: Technical Aspects Of Hcc Biomarker Developmentmentioning
confidence: 99%
“…We do not cover interventional applications, as they are described by several other recent review papers [ 11 , 21 , 22 ]. We do not cover point-of-care body MRI systems [ 23 ], such as the prostate [ 24 ], or liver [ 25 , 26 ] scanners, because these systems operate at a much lower field strength (< 0.1 T) and are designed for a single or a few applications, and are, therefore, not suitable for general-purpose body imaging. The results discussed in this paper come primarily from whole-body systems such as the 0.35 T (Viewray) [ 14 ], 0.55 T (“ramped down” Siemens Aera [ 11 ] and Siemens Free.Max [ 12 ]), and 0.75 T (“ramped down” Philips Achieva) [ 13 ], with specifications listed in Table 2 .…”
Section: Introductionmentioning
confidence: 99%